Controller synthesis with compensation AW and performance in H2-Hâˆž - Ríos Bolívar, Addison (Rev. Téc. Fac. Ing. Univ. Zulia)
Considering the time invariant linear systems (LTI), this contribution studies the design problem of robust Anti-Windup compensation (AW). The robust performance is analyzed on two function transfers of closed loop using the H2-Hoo norms. One transfer function is defined of the controlled output respect to the perturbation, in order to design a dynamical controller, minimizing the H2 norm. Another one transfer function from the actuator output to the controller output is used in order to evaluate the performance under saturation. The performance index considers the effect of the saturation on the controller output, and this index allows to design the AW compensation gain, minimizing the H_ norm. The dynamical controller and the AW compensation gain are obtained by numerical solution of linear matrix inequalities (LMI), which allow to characterize the H2- Hoo norms.